Tracking climate adaptation in hospitals: An inventory of structural measures - Louise Elstow; Felipe Rojas Parra; Kristen MacAskill (Climate Risk Management)
Adaptation plays a critical role in reducing risks from climate change and the need for climate adaptation is increasingly being recognised in national policies. However, evidence of coherent action at sector level is varied and often lacking. This paper critically examines climate adaptation action taken in the health sector. This involved collecting and analysing data for an inventory of hospital-based cases, retrieved from scholarly and grey literature. This process highlighted a paucity of reporting on such interventions, which are not yet well-covered in wider efforts for sustainability or climate action reporting. We found 125 examples of implemented structural measures intended to adapt hospital facilities to respond more favourably to anticipated changes in climate. The inventory provides insight into what adaptation actions are being reported across regions around the world and the motivations behind them, which provides a basis for considering how business cases are being made for these investments.Doing so means we are able to make three contributions to the field of climate adaptation. First, our analysis of the initial data highlights nascent trends, for example, experience of a previous weather event or adherence to current building codes are the two dominant motivating factors for pursuing adaptation. Second, identifying the challenges involved in gathering and compiling adaptation data has implications for the field of climate adaptation itself, and the data needed to drive decision making and better understanding of what is happening. Notably, the evidence collected from various regions contain biases attributed to data retrievability, where North American examples are most readily available. Finally, it is anticipated that the inventory—which provides a baseline for categorising interventions in the sector—has value for generating understanding of what comprises adaptation practice, beneficial to both hospital practitioners and researchers alike.